Oral Histories of a Layered Landscape: The Rushworth Oral History Project - Keir Reeves; E. Rebecca Sanders; Gordon Chisholm (Public History Review, 2007)
This article reflects the authors’ experience of undertaking an oral history project in the regional Victorian town of Rushworth. The authors of the article contend that to conduct an investigation of the natural and cultural heritage of the town and surrounding forests is also to engage in an archaeology of historical landscapes. The authors, after articulating the theoretical and methodological issues of oral history, name and trace the various historical layers of the landscape of Rushworth and the forest that surrounds the town. They argue that the use of oral history in conjunction with cultural landscape analysis enables a deeper understanding of the cultural complexity of the history of Rushworth and the surrounding region. Broader issues concerning regional identity and the role of historians in providing a greater understanding of the community in the present day are also evaluated.